ICT Adoption and VAT Registration among Unincorporated Enterprises in India: Analysis of Unit-Level Data. Issue 2 (December 2021) - Badola, Shivani; Mukherjee, Sacchidananda
Introduction of Goods and Services Tax (GST) has resulted in harmonisation of tax compliance system in India. In the new tax regime, tax compliance system has completely moved to online (digital) platforms. Given the inequality in access to digital platform or adoption of Information and Communications Technology (ICT) among marginal, small and medium enterprises in India, tax compliance may not improve in the GST regime. In a developing country like India where majority of unincorporated enterprises are in the informal sector, staying outside the formal network may restrict their economic prospects. It is worthwhile to study the relationship between access to ICT and tax (VAT) registration among unincorporated enterprises in India. Based on unit-level data of the 73rd round NSS survey, this study explores factors influencing the decision of unincorporated enterprises to take VAT/Sales Tax registration across the Indian states. The results show that adoption of ICT in terms of using internet and computers positively influence tax registration. Policy suggestions of the study may help to expand the tax base of GST by bringing informal enterprises under the tax net.